Preliminary study of utilizing a patient derived tumor spheroid model to augment precision therapy in metastatic brain tumors - Chun-Jen Chang; Kai-Wen Kan; Yu-Yin Shih; Yu-Han Nan; Yu-Chung Juan; Chih-Hsiu Tu; Chen-Ting Yang; Wei-Lin Hsu; Der-Yang Cho; Ming-You Shie; Yi-Wen Chen; Chun-Chung Chen (Scientific Reports)
Abstract Treating metastatic brain tumors remains a significant challenge. This study introduces and applies the Patient-Derived Tumor Spheroid (PDTS) system, an ex vivo model for precision drug testing on metastatic brain tumor. The PDTS system utilizes a decellularized extracellular matrix (dECM) derived from adipose tissue, combined with the tumor cells, to form tumor spheroids. These spheroids were subsequently used to test anticancer drugs, with results compared to the clinical outcomes observed after administering these treatments to patients. To assess the validity of the data, the correlation between the drug responses observed in the PDTS model and actual patient outcomes was analyzed. Chi-square tests evaluated the significance of associations between lab predictions and clinical outcomes, using a significance threshold of p < 0.05. In preliminary data, 17 patients met the criteria for final analysis, which showed an overall 57% accuracy (p-value = 0.463), with improvements to 73% accuracy (p-value = 0.072) when patients receiving certain treatments were excluded. This PDTS offers real-time results within three weeks, simultaneous testing of multiple drugs, and the ability to culture and store tumor cells for reproducibility. Despite some limitations, further development of this model could enhance its clinical application and improve patient outcomes.